SPIRITUAL WELL-BEING AS PREDICTOR OF PARENTING STRESS AND SOCIO-ECONOMIC BACKGROUND AS MODERATOR IN MOTHERS OF CHILDREN WITH AUTISM - matuzahroh, Ni’; Rohmah, Nazilah Nikmatin; Chou, Mei-Hsiu; Suen, Mein-Woei; Shieh, Fu-An (International Journal of Psychosocial Rehabilitation, 2020)
Objective: Parents with autistic children often experience parental stress because caring for them requires different treatment compared to caring for healthy children. Spiritual well-being is one of the factors that can reduce parenting stress levels. The purpose of the current study was to explore the relationship of parenting stress and spiritual well-being as a protective factor for parenting stress and socioeconomic status that thought to influence the relationship between the two.Methods: This research is a quantitative study using a purposive sampling technique. Participants in this study were 42 mothers who have autistic children. The data collection method in this study was used a spiritual well-being scale, parenting stress scale, and a socioeconomic status questionnaire test. Analysis of data using moderated regression analysis (MRA).Results: The results showed that parenting stress has a significant negative relationship with spiritual well-being and parenting stress (B = -0.686; p 0.05).Conclusions: Spiritual well-being has a negative and significant relationship to parenting stress. It shows that if the subject has a high spiritual well being, the parenting stress is low and vice verse. Then if there are socioeconomic status factors that enter, it can not strengthen the spiritual well-being and parenting stress relationship. It shows that the social-economic level of the subject does not affect the level of spiritual well being or parenting stress on the subject.